Effect of Hot-Rolled Heavy Section Bars Post-Deformation Cooling on the Microstructure Refinement and Mechanical Properties of Microalloyed Steels - Monika Banasiak; Andrzej Hornik; Stanisław Szczęch; Janusz Majta; Marcin Kwiecień; Agnieszka Cebo-Rudnicka; Marcin Rywotycki; Krzysztof Muszka (Metals, 2021)
In the industrial practice—especially in the reverse rolling mills—heavy section products with stable mechanical properties (YS, UTS) and ductility (A, Z) but with an impact toughness (KV) at too low levels are often observed. The results presented in the present work concern the relationship between the parameters of the cooling process of rolled products made of microalloyed steels, with different chemical compositions (such as Al-N, Al-N-V, Al-N-Ti) and their mechanical properties. Special focus was put on the relationship between chemical composition, grain size and impact toughness at subzero temperatures. It is shown, that by introducing the restrictions towards more strict control of the levels of Al, Ti, V, and N, it can be ensured that the final parameters are not that sensitive to process parameters variations which, hence, provides the required mechanical properties and especially impacts on the toughness requirements for a wide range of section products. It was also found that by slight modifications of microalloying elements and proper control of the process parameters, it is possible to replace commonly used normalizing annealing heat treatment after rolling with normalizing rolling.